A new Environmental Poverty Index (EPI) for monitoring system in the SEA (Strategic Environmental Assessement) procedure - Hoe, Nguyen Dinh (VNU Journal of Science: Earth and Environmental Sciences; Vol 24 No 4, 2008)
Abstract